Anthropology in the East : founders of Indian sociology and anthropology - Uberoi, Patricia; Sundar, Nandini; Deshpande, Satish (Seagull Books, 2008)
Contributed seminar articles on some of the founding figures of anthropology and sociology in India, held at the Institute of Economic Growth, Delhi, Apr. 19-21, 2000.